Clinical Manifestations and Outcomes of Syphilis-associated Uveitis in Northern Spain. (3rd March 2016) - Fonollosa, Alex; Martinez-Indart, Lorea; Artaraz, Joseba; Martinez-Berriotxoa, Agustin; Agirrebengoa, Koldo; Garcia, Miriam; Lopez-Soria, Leire; Sorribas, Manuel; Diaz-Valle, David; Blanco, Ricardo; Rueda-Gotor, Javier; Adan, Alfredo; et al.
Abstract: Purpose : To describe the clinical characteristics and to assess visual prognosis of patients with syphilis-associated uveitis in northern Spain. Methods : Retrospective review of clinical records in eight general uveitis referral centers. Results : Since the year 2000, 50 patients have been diagnosed: 31 men and 19 women; median age was 41 (19–76) years. A total of 34% were co-infected with HIV and 24% presented systemic manifestations of syphilis. Median initial visual acuity and vision at last visit in 93 affected eyes was 20/50 (20/20–20/2000) and 20/22 (20/20–20/2000), respectively ( p  < .0001). The most frequent manifestation was papillitis (33.3%). Fifty percent of eyes with macular edema on admission presented worsening of visual acuity at last visit, whereas frequency of worsening in eyes without edema was 7.1% ( p  = 0.009). Conclusions : In our series, patients with syphilitic uveitis were more usually middle-aged men and were frequently co-infected with HIV. Although most patients showed posterior segment involvement, visual prognosis was good.